2011
DOI: 10.1073/pnas.1100640108
|View full text |Cite
|
Sign up to set email alerts
|

Core promoter recognition complex changes accompany liver development

Abstract: Recent studies of several key developmental transitions have brought into question the long held view of the basal transcriptional apparatus as ubiquitous and invariant. In an effort to better understand the role of core promoter recognition and coactivator complex switching in cellular differentiation, we have examined changes in transcription factor IID (TFIID) and cofactor required for Sp1 activation/Mediator during mouse liver development. Here we show that the differentiation of fetal liver progenitors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 43 publications
4
33
2
1
Order By: Relevance
“…8B). Thus, the maturation of T cells is not accompanied by a change in TFIID composition, as has been reported in other systems (12,11). …”
Section: Taf7-deficient Dn Thymocytes Have a Defect In Proliferationsupporting
confidence: 78%
See 1 more Smart Citation
“…8B). Thus, the maturation of T cells is not accompanied by a change in TFIID composition, as has been reported in other systems (12,11). …”
Section: Taf7-deficient Dn Thymocytes Have a Defect In Proliferationsupporting
confidence: 78%
“…For example, it has been reported that during the differentiation of myoblasts to myocytes, multiple TFIID components, including TBP, are lost (12). Similarly, the requirement for TAFs changes during hepatocyte development (11). Cell type-specific requirements for TAFs, such as TAF10, have been reported in other systems (20,25,35).…”
Section: Discussionmentioning
confidence: 99%
“…We performed MS analysis of human and mouse cultured erythroid progenitor cells at an immature stage (proerythroblasts) and upon differentiation, which revealed that most of the TFIID and SAGA subunits are present in these complexes at all stages analyzed. Our data exclude the possibility of a total rearrangement of the TFIID or SAGA complexes in this differentiation system, in contrast to what was reported for TFIID during liver hepatocyte (64) or myoblast (65) differentiation. Nevertheless, during differentiation we observed a dynamic reorganization of some TFIID and SAGA subunits, usually affecting those that have paralogues, such as TAF4/TAF4b, TAF9/TAF9b, GCN5/PCAF, and ATXN7/ATXN7L1/ATXN7L2, without affecting the core structure of these complexes.…”
Section: Discussioncontrasting
confidence: 81%
“…In support of this, it appears that the subunit composition of Mediator is simplified in differentiated cells 13,14 . Whereas the phenomenon of simplified subunit composition in differentiated cells is best defined for the multi-subunit transcription factor IID (TFIID) complex 15 , smaller Mediator complexes with fewer than the typical 26 subunits would also likely adopt more specialized functions.…”
Section: Mediator Composition and Structurementioning
confidence: 75%